Femtosecond IR Laser Inscription of Bragg Gratings in Single- and Multimode Fluoride Fibers - Grobnic, D.; Mihailov, S.J.; Smelser, C.W. (IEEE photonics technology letters, 2006)
We report for the first time the fabrication of fiber Bragg gratings in both single- and multimode undoped fluoride fibers using femtosecond 800-nm radiation and a phase mask. Grating spectra are presented along with an evaluation of the grating behavior at high temperature. Index changes of ~2times10 -4 are achieved